An Approach to the Presence (or Absence) of Galician and Its Literature in Denmark: Academia, Translation and Awareness - Rodríguez Tembrás, Vanesa (Madrygal. Revista de Estudios Gallegos, 2015)
This study focuses on exploring the influence of Galicia, its literature and its culture, in Denmark. On realizing a lack of awareness and an absence of our language in the Danish academic circles, their publishers and other social circles, we ascertain the weaknesses and strengths of a possible implementation of Galician and its literature in Denmark.